Mortality indicators of COVID–19 in high burden states and cities of India: a review - G., Srinivas; T. K., Sivabakya; A., Rakesh; S., Valarmathi; Seshayyan, Sudha (International Journal Of Community Medicine And Public Health, 2020)
Understanding the dynamics of COVID-19 case-fatality and recovery rates would strengthen the knowledge base on the current trends of the epidemic’s severity. During the outbreak, the case-fatality ratio (CFR) is commonly used in most countries. On average it raised from 3.4 percent (as of 25 February 2020) across countries to 7.0 percent (as of 21 April 2020) and then came down to 3.91 percent (as on 31st July 2020). This review was conducted according to the preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines. The articles were searched from databases like PubMed, the Cochrane library and Science Direct combining MeSH and free-text terms. In India, the states of Maharashtra and Madhya Pradesh had higher CFR levels as against the southern states of Kerala and Tamil Nadu with significantly lower CFR. India’s total number of COVID-19 fatalities per million population is one of the lowest in the world measuring 27.02 per million. Weekly death rate measures of India are lowest affecting 0.29 per 1000 inhabitants. Of the major cities of India, Chennai showed upward trend with a highest weekly death rate in the last week of July 2020, accounting for 2.02 deaths per 1000 inhabitants. This article attempts to provide an over view of key mortality indicators to measure COVID-19 deaths and assess the mortality trends of selected cities and states in India during the months of June and July 2020.